Rhetorical Study of Ideological Representation in Public Discourse: A Critical Analysis of Socio-Cultural Discourse: Studi Retorika Atas Representasi Ideologi Dalam Wacana Masyarakat: Analisis Kritis Terhadap Diskursus Sosial Budaya - Akmal Fajri (Pusaka Cendekia Indonesia Foundation, 2025)
This study examines rhetoric as a medium of ideological representation in public discourse, focusing on Anies Baswedan's speech delivered at the Gadjah Mada University (UGM) Campus Mosque in the month of Ramadan. Rhetoric, both in the classical Arabic tradition (al-balāghah) and in the modern context, is understood not only as the art of speech, but also as an instrument for shaping social meaning, defending or challenging ideology, and reproducing symbolic power. In contemporary society, public discourse serves as a strategic arena in the formation of collective consciousness and social legitimacy. This study uses the three-dimensional Critical Discourse Analysis (CDA) approach from Norman Fairclough: text analysis, discourse practice, and social practice. The method used is qualitative-descriptive with the main data in the form of transcripts and video documentation of speeches. Data collection techniques are carried out through documentation and literature studies, while analysis is carried out in three stages: linguistic description, interpretation of the context of discourse production and consumption, and socio-ideological explanation. The results of the study show that Anies Baswedan's speech contains rhetorical strategies that represent religious values, education, and integrity, and succeed in combining academic and socio-cultural symbolic spaces as a means of ideological legitimacy and the formation of collective perceptions. These findings confirm that rhetoric in public discourse plays an important role in the production and distribution of ideology in society. Penelitian ini mengkaji retorika sebagai medium representasi ideologi dalam wacana publik, dengan fokus pada pidato Anies Baswedan yang disampaikan di Masjid Kampus Universitas Gadjah Mada (UGM) pada bulan Ramadhan. Retorika, baik dalam tradisi klasik Arab (al-balāghah) maupun dalam konteks modern, tidak hanya dipahami sebagai seni berbicara, tetapi juga sebagai instrumen untuk membentuk makna sosial, mempertahankan atau menantang ideologi, serta mereproduksi kekuasaan simbolik. Dalam masyarakat kontemporer, wacana publik berfungsi sebagai arena strategis dalam pembentukan kesadaran kolektif dan legitimasi sosial. Penelitian ini menggunakan pendekatan Analisis Wacana Kritis (AWK) model tiga dimensi dari Norman Fairclough: analisis teks, praktik wacana, dan praktik sosial. Metode yang digunakan bersifat kualitatif-deskriptif dengan data utama berupa transkrip dan dokumentasi video pidato. Teknik pengumpulan data dilakukan melalui dokumentasi dan studi pustaka, sedangkan analisis dilakukan dalam tiga tahap: deskripsi linguistik, interpretasi konteks produksi dan konsumsi wacana, serta eksplanasi sosial-ideologis. Hasil penelitian menunjukkan bahwa pidato Anies Baswedan mengandung strategi retoris yang merepresentasikan nilai-nilai keagamaan, pendidikan, dan integritas, serta berhasil menggabungkan ruang simbolik akademik dan sosial budaya sebagai sarana legitimasi ideologis dan pembentukan persepsi kolektif. Temuan ini menegaskan bahwa retorika dalam wacana publik memainkan peran penting dalam produksi dan distribusi ideologi dalam masyarakat.